Peran Harga, Brand Image dan Inovasi Produk dalam Meningkatkan Loyalitas Pelanggan Studi Kuantitatif pada Konsumen Motor Honda di Kabupaten Purworejo - Dwi Rahmadani, Anisa; Hesti Respatiningsih; Anna Probowati (CV. ALIM'SPUBLISHING, 2026)
This study aims to examine the influence of price, brand image, and product innovation on the level of customer loyalty of Honda motorcycles, especially in Purworejo Regency. The method used in this study is a quantitative approach with an explanatory design. Data collection was carried out by distributing questionnaires to 100 respondents with the following requirements: a minimum of 17 years old, domiciled in Purworejo Regency, have used or owned a Honda motorcycle for at least 1 year, and selected using a purposive sampling technique. Then the data obtained were analyzed using multiple linear regression with the help of IBM SPSS Statistics 25. Before being analyzed, validity and reliability tests were conducted to determine the instrument can be used and a classical assumption test was conducted to ensure that the regression model meets statistical requirements. The results of the research analysis simultaneously show that price, brand image, and product innovation have a significant influence on customer loyalty. However, this is different from the partial test which indicates that only brand image has a significant influence in shaping customer loyalty. Brand image was also found to be the most dominant factor in increasing the tendency to repurchase, resistance to competing brands, and positive customer recommendations.